Linguistic and Cultural Aspects of Studying New Vocabulary in Conditions of Globalization (Proceedings of Southern Federal University. Philology, 2019)
Veronika V. Katermina, Sofia Ch. Lipiridi  (Krasnodar, Russian Federation)The article examines linguocultural potential of neologisms in English discourse. Neologisms taken as a whole reflect the spirit of time, the unity of meanings, values and stereotypes inherent in a particular society in a specific cultural and historical period of its existence. The linguocultural approach which implies consideration of neologisms that reflect linguocultural specificity, the mentality of representatives of any culture has been used in the article. This approach gives prominence to the linguocultural analysis which involves the study of neologisms when using cultural information to interpret the facts relating to these neologisms extracting this cultural information. Neologisms transmit data of socio-historical, expressiveemotional, evaluative nature inherent in a particular culture. Such units of information constitute the national-cultural component in the structure of the word. Individual ethnocultures have certain universals due to the presence of similar features in the socio-historical conditions of human development. However, there are a great number of differences associated with a particular culture. The article emphasizes that being national-specific neologisms, through their space, implement categories which representatives of different people think in and the boundaries in which they are set for the purpose of perception and analysis of the surrounding world.Key words: language, culture, neologism, cultural linguistics, cultural and linguistic value component, linguocultural potential.DOI 10.23683/1995-0640-2019-4-31-39